Corrigendum: Evaluation of Anticoagulant Use in Post Valvular Heart Surgery in Relation with International Normalised Ratio (INR) and Valve Replaced - Rathore, Mahendra Singh (Indian Journal of Pharmacy Practice)
Evaluation of Anticoagulant Use in Post Valvular Heart Surgery in Relation with International Normalised Ratio (INR) and Valve Replaced